Volcanic-subvolcanic rocks and tectonic setting of the Zhengguang intermediate sulfidation epithermal Au-Zn deposit, eastern Central Asian Orogenic Belt, NE China. (1st October 2018) - Wang, Le; Qin, Kezhang; Song, Guoxue; Pang, Xuyong; Li, Zhenzhen; Zhao, Chao; Jin, Luying; Zou, Xinyu; Li, Guangming
Graphical abstract: Highlights: Zhengguang is an intermediate sulfidation epithermal deposit formed in a continental arc. Zhengguang is the oldest IS deposit in the world and the oldest epithermal deposit in CAOB. Adakitic dacite porphyry formed from partial melting of the subducted oceanic plate. Intermediate dikes contain low Mg-andesitic rocks and high Mg-andesitic rocks. Neoproterozoic continental crust growth is present in the Duobaoshan area. Abstract: The Zhengguang Au-Zn deposit is a large epithermal deposit adjacent to the Tongshan and the Duobaoshan porphyry Cu deposits in the Duobaoshan ore field, NE China. The host rocks mainly consist of andesite, andesitic tuff, and volcanic breccia. There are also many diorite dikes and subvolcanic rocks, including dacite porphyry and andesite porphyry. This contribution presents the zircon U-Pb ages, whole rock elemental and Sr-Nd isotopic compositions and zircon in situ Hf isotopic data for volcanic and subvolcanic rocks at Zhengguang. The dating results show that there are at least three episodes of magmatic events in the Zhengguang area: first, the extrusion of main host andesite of the Duobaoshan Formation (>490 Ma); second, the emplacement of copious andesitic dikes (490–470 Ma); and finally, early Silurian intermediate magmatic activity (440–436 Ma). The dacite porphyry emplaced at 480 Ma has relatively high SiO2 (63.5–64.7 wt%) and Sr (250–324 ppm) content, low Yb (0.59–0.67 ppm) and Y (5.65–6.63 ppm) content, and low initial 87 Sr/ 86 Sr ratios (0.7026–0.7031), suggesting an adakitic affinity. Given the positive εNd(t) values (+6.1 to + 7.1), εHf(t) values (+7.5 to + 13.5), high Mg# values (61–62), slightly high content of Cr (87.7–92.6 ppm), and Ni (37.6–46.9 ppm), we propose that the porphyry was derived from partial melting of subducted slabs of the Paleo-Asian oceanic plate with input from the mantle wedge during the ascent. The intermediate rocks can be divided into low Mg-andesitic rocks (LMAR, Mg# 33–54, Cr 14–144 ppm, and Ni 4–39 ppm) that originated from partial melting of the juvenile lower crust underplated by the mantle wedge-derived magma and high Mg-andesitic rocks (HMAR, Mg# 58–76, Cr 217–774 ppm, and Ni 81–419 ppm) derived from the partial melting of the slab fluid-metasomatic mantle wedge. The statistics of TDM2 of zircon Hf suggest that certain amounts of Neoproterozoic (particularly 800–600 Ma) continental crust growth were involved in the eastern part of the Central Asian Orogenic Belt (CAOB), as evidenced in the Zhengguang area. Based on the geological relationship and mineralization style, we suggest that the Zhengguang deposit is an intermediate sulfidation epithermal deposit formed at ca. 480 Ma in a continental arc setting. Our work shows that Zhengguang is the oldest epithermal deposit in the CAOB and the oldest intermediate sulfidation (IS) epithermal deposit in the world. The identification of these characteristics is important for better understanding epithermal deposits in China and will add new insights about prospecting IS deposits in similar tectonic settings, especially in the CAOB.